Exploring The Relationship Between Moot Court Participation and Legal English Proficiency - Anh, Nguyen Hai (Lia Center of Research and Education, 2025)
This study investigated the potential association between moot court participation and legal English proficiency among law students in a non-native English-speaking context, specifically at Hanoi Law University (HLU) in Vietnam. Employing a mixed-methods design, quantitative surveys were administered to 60 international trade law students who had participated in moot court activities, while semi-structured qualitative interviews were conducted with 15-20 of these participants to explore their experiences, perceptions, and motivations. Findings suggest an association between moot court involvement and perceived improvements in legal English skills, with participants reporting enhanced confidence in legal communication (mean score 4.00 on a 5-point scale) and a statistically significant difference in proficiency scores across participation levels (ANOVA: F(2,57)=50.68, p<.001). However, results rely on self-reported data and correlational analyses, limiting causal inferences, and findings may not generalize beyond HLU. The study recommends targeted integration of moot court into legal English curricula, provision of support resources, and further research with objective measures to enhance skill development.